Exploring the Indonesian Nursing Students’ Difficulties in Answering the TOEFL Prediction Test - Dedi Jasrial; Wisma Yunita; Ade Sissca Villia (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
The TOEFL is a type test known internationally to assess someone’s proficiency in English language. However, many EFL students have problems in doing the TOEFL test so that their score results are still under the minimum score. The aim of this study is to explore the nursing students’ difficulties in answering the TOEFL questions. This study was a descriptive-quantitative study that involved fifty-one nursing students of the Poltekkes Kemenkes Bengkulu. The data of this study were gathered by using a questionnaire in the form of Google form based on Likert’s scale. The results of the study revealed that the level of difficulty experienced by the nursing students in answering the questions on the TOEFL test was in a high category. The listening comprehension section gained the mean score of 3.79, the structure and written expression section gained the mean score of 3.67, and the reading comprehension section gained the mean score of 3.62. Moreover, their difficulties were in a high category for all of the items in the questionnaire. In brief, the difficulties faced by the nursing students show that their English proficiency is still low.